States of liberation : gay men between dictatorship and democracy in Cold War Germany - Huneke, Samuel Clowes (German and European studies., 2022)
"States of Liberation traces the paths of gay men in East and West Germany from the violent aftermath of World War II to the thundering nightclubs of present-day Berlin. In this groundbreaking account of male homosexuality in Cold War Germany, Samuel Clowes Huneke uncovers how the history of gay persecution and liberation continues to shape life in reunified Germany today. Following a captivating cast of characters, from gay spies and Nazi scientists to queer politicians and secret police bureaucrats, States of Liberation tells the remarkable story of how the two German states persecuted gay men--and how those men slowly, over the course of decades, won new rights and created new opportunities for themselves in the heart of Cold War Europe. Relying on untapped archives in Germany and the United States as well as oral histories with witnesses and survivors, Huneke reveals that communist East Germany was in many ways far more progressive on queer issues than democratic West Germany. States of Liberation fundamentally argues for a more nuanced understanding of gay liberation and its relationship to democracy and dictatorship in the modern world."--